Annotations : on the early thought of W. E. B. Du Bois - Chandler, Nahum Dimitri (Duke University Press, 2023)
"Annotations is a close study of the philosophical dimensions of the early thought of W. E. B. Du Bois with regard to the idea of human differences and on historicity. Nahum Chandler puts forward a thorough and annotative interpretation of W. E. B. Du Bois's 1897 Negro Academy address "The Conservation of Races." In this early speech, which Chandler sees as a signal text, Du Bois examines the idea of race, and the way Africa and its diasporas have been considered by history. The interpretation is organized into two parts, the first being a paragraph by paragraph interpretation and the second being a meditation on Du Bois's ideas of history and historicity. Over the course of the book, Chandler uses the critical practices of Jacques Derrida to develop a critical hermeneutic of this address and, in doing so, refigures how we think about the lineage of Du Bois's thought. Chandler argues that the address prompts a reimagining of historicity, especially in the context of the historical development of the concept of human and the significance of space and time to that development"--